2022
DOI: 10.1002/slct.202203050
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles, Synthesized using Hyptis suaveolens (L) Poit and their Antifungal Activity against Candida spp.

Abstract: Silver nanoparticles (AgNPs), due to their interesting properties and many potential applications have attracted enormous interests in recent years. An attempt has been made in this present study to synthesize AgNPs through biological reduction of silver nitrate, with leaf extract of Hyptis suaveolens (L) Poit serving as a reducing agent. AgNPs formed were characterized with spectral (UV-Vis, XRD, FTIR) and electron microscopic investigations. Dispersed spherical nanosilver particles in the range of 2 nm-85 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Achieving stable AgNPs was accomplished by employing a 0.25 % concentration of ketepeng leaf extract, resulting in a singular peak at the maximum wavelength of 439 nm. In a reported study, the synthesis of AgNPs has been confirmed through monitoring with UV‐visible spectroscopy, revealing a distinct characteristic at 435 nm [38] …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Achieving stable AgNPs was accomplished by employing a 0.25 % concentration of ketepeng leaf extract, resulting in a singular peak at the maximum wavelength of 439 nm. In a reported study, the synthesis of AgNPs has been confirmed through monitoring with UV‐visible spectroscopy, revealing a distinct characteristic at 435 nm [38] …”
Section: Resultsmentioning
confidence: 84%
“…In a reported study, the synthesis of AgNPs has been confirmed through monitoring with UV-visible spectroscopy, revealing a distinct characteristic at 435 nm. [38] It is noteworthy that according to reported studies, indicates that particle size determination can be established through the application of the Mie theory (Equation ( 1)). [39,40] d ¼…”
Section: Green Synthesis Of Agnps Using Ketepeng Leaf Extractmentioning
confidence: 99%